Accuracy Analysis of the Aerosol Backscatter Coefficient Profiles Derived from the CYY-2B Ceilometer - Lei Liu; Ting Zhang; Yi Wu; Qi Wang; Taichang Gao (Advances in Meteorology)
Ceilometers are originally designed for cloud base height monitoring. Since a few years, the number of ceilometers available worldwide is rapidly increasing, and these simple backscatter lidars are investigated to be used for aerosol research. This study presents an assessment of the potential of CYY-2B ceilometer for the quantitative retrieval of aerosol properties. The signal-to-noise ratio of the ceilometer is calculated, and the effective height of inversion is determined. It is shown that the effective height of the ceilometer for backscatter coefficient profile inversion is 3-4 km at night and about 1.5–2 km during the day, which is lower than that of the micropulse lidar (MPL) system. The accuracy of the backscatter coefficient profiles derived from the CYY-2B ceilometer is analyzed by using the Vaisala CL51 ceilometer, MPL, forward scatter visibility instrument, and aerosol optical depth (AOD) dataset from aerosol robotic network (AERONET). Spectral conversions of the ceilometer’s and lidar’s data are performed using the Ångström exponent estimated by AERONET measurements. A good agreement is found between two ceilometers and the MPL lidar in backscatter coefficient profiles inversion. The AODs agree well with the AERONET AODs during the observation period of small AODs. However, for the period of large AODs, the results are approximately 50%–60% of AERONET AODs. The limited range of extinction integration is the main cause of this problem.